KOMUNIKASI SOSIAL ANTARA WARGA BELAJAR PROGRAM PAKET C DALAM MENINGKATKAN AKTIVITAS BELAJAR DI PKBM INSAN CENDEKIA KELURAHAN SIALANG MUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - Fitria Eka Putri; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out social communication between community learning C package program in improving learning activities at Insan Cendekia community learning centre Sialang Munggu Kecamatan Tampan Pekanbaru. The formulation of the problem of this research is social communication among residents learning program c package in improving learning activities in Insan Cendekia community learning centre Sialang Munggu Tampan Pekanbaru is good. The population in this study as many as 31 residents learn. the researchers used a saturated sample so that all the population in the sample made as many as 31 residents of community learning centre Insan Cendekia Sialang Munggu Village Tampan District Pekanbaru, and 20 people for trials in community learning centre Pucuk rebung Pekanbaru. The type of this research is descriptive with quantitative approach. The data collection instrument is a questionnaire with 113 statements and after the trial live 103 valid statements to be made in the research instrument. Data analysis through quantitative descriptive analysis. The findings of this study indicate that social communication between citizens learn the package c program in improving the learning activities in community learning centre Insan Cendekia Sialang Munggu Tampan, Pekanbaru that the highest is interpersonal communication with 63.1% percentage means that citizens learn to have good communication between fellow citizens learning in learning activities.Keywords: Social Communication, Learning Activity, C Package.